Customer Adoption of Banking Technology in Private Banks of India - Tater, Bindiya; Tanwar, Manish; Murari, Krishna (Universiti Utara Malaysia, 2011)
This paper explores the perception of Indian customers towards the use of technologies with respect to such factors as convenience, privacy, security, ease of use, real time accessibility, and accurate record of varied transaction that enable customer’s adoption of Banking Technology. Other factors such as slow transfer speed, technical failure, frauds and unawareness among customers that make hindrance in adoption, are also tested. The results show that demographic variables such as gender, age, qualification and income play a positive role in adoption of banking technology. All the banks are using information technology as a strategic vehicle to stay competitive against other players. There is no significant difference between adoption rates of banking technologies by the customers of different private banks. The paper also shows that banking technology helps in increasing customer satisfaction, customer loyalty, improvised growth, and performance of the banks.